Study the Effect of Using Low-Cost Dielectric Lenses with Printed Log-Periodic Dipole Antennas for Millimeter-Wave Applications - Osama M. Haraz; Abdel Razik Sebak; Saleh Alshebeili (International Journal of Antennas and Propagation)
Design of V-band high-gain printed log periodic dipole array (PLPDA) antenna loaded with a low-cost spherical dielectric lens is introduced. The proposed antenna consists of microstrip-line-fed log-periodic dipole antenna designed to operate in the V-band with a peak gain of 12.64 dBi at 60 GHz. To enhance the antenna gain, a dielectric lens is installed. The antenna prototype is fabricated and then tested experimentally using Agilent E8364B PNA Network Analyzer. Experimental results agree well with the simulated ones. The simulated results show that the proposed antenna can work from 42 GHz up to 82 GHz with a fractional impedance bandwidth of 64.5% covering the whole V-band (50–75 GHz). At 60 GHz, the proposed antenna has peak gain of 26.79 dBi with a gain variation of 3.5 dBi across the whole V-band with stable radiation patterns over the operating band. The proposed PLPDA antenna achieves good side-lobe suppression, excellent front-to-back ratio in both E- and H-planes, and low cross-polarization levels over the entire frequency range. These unique features will make this antenna suitable for different interesting applications such as millimeter-wave radar and imaging applications.